Advances in Drug Delivery Systems for Osteochondral Tissue Regeneration - Jun Shang; Jianping Zhang; Linhong Liu; Wenjuan Kou; Pingping Zhang; Guangwei Sun; Huishuang Zhou; Weihan Shi; Yaning Zhang; Chaozong Liu; Bin Li (BIO Integration)
Osteochondral damage is primarily caused by degeneration of articular cartilage due to trauma, degenerative injury. Current approaches to treating cartilage damage typically involve medications, physical therapy, interventional therapy, and surgery. Drug delivery to the cartilage has shown promise in cartilage regeneration and slowing the progression of cartilage degeneration. However, the unique physiologic composition of articular cartilage poses challenges for effective drug delivery. Systemic administration of drugs may lead to inadequate drug distribution within the cartilage. Direct intra-articular injection of drugs can result in rapid clearance and limited retention time of the drug in the joint cavity. In summary, the limited duration of drug efficacy within the joint due to a short half-life and restricted diffusion through cartilage poses challenges for long-term drug therapy. Surgical intervention becomes necessary in cases of severe joint degeneration or ineffectiveness of alternative treatments. Various clinical studies have demonstrated the effectiveness of surgical approaches, such as an osteochondral autograft transplantation system (OATS), autologous chondrocyte implantation (ACI), and microfracture. Unfortunately, these interventions are also associated with potential adverse effects. The ongoing advances in biomaterials for osteochondral tissue regeneration and replacement have led to a growing interest in the utilization of biomaterial-based drug delivery systems for tissue regeneration. The integration of bioactive molecules, drugs, and genes with biomaterials presents a novel strategy for advancing osteochondral regeneration. A desirable drug delivery system should be able to penetrate cartilage tissue before the drug is cleared by synovial capillaries and lymphatic vessels, and bind to components of the cartilage extracellular matrix to reduce the physical deformation of cartilage during locomotion, resulting in a cartilage-specific drug pool. This paper was motivated by the great potential of biomaterials for osteochondral tissue regeneration and reviews recent progress in biomaterial-based drug delivery systems for osteochondral regeneration.